2017
DOI: 10.3389/fphar.2017.00034
|View full text |Cite
|
Sign up to set email alerts
|

Morus alba Leaf Lectin (MLL) Sensitizes MCF-7 Cells to Anoikis by Inhibiting Fibronectin Mediated Integrin-FAK Signaling through Ras and Activation of P38 MAPK

Abstract: Lectins are a unique class of carbohydrate binding proteins/glycoproteins, and many of them possess anticancer properties. They can induce cell cycle arrest and apoptosis, inhibit protein synthesis, telomerase activity and angiogenesis in cancer cells. In the present study, we have demonstrated the effect of Morus alba leaf lectin (MLL) on anoikis induction in MCF-7 cells. Anoikis induction in cancer cells has a significant role in preventing early stage metastasis. MLL treatment in monolayers of MCF-7 cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…FAK is a member of the focal adhesions that mediates integrin-mediated signal transduction associated with a variety of cellular functions including cellular proliferation, migration, and adhesion. The downstream signaling pathways involved in FAK signaling include the Jun N-terminal kinases (JNK) survival pathway, and the phosphoinositide 3-kinase (PI3K)/Akt pathway [ 17 ]. PI3K/Akt controls cell proliferation, survival, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…FAK is a member of the focal adhesions that mediates integrin-mediated signal transduction associated with a variety of cellular functions including cellular proliferation, migration, and adhesion. The downstream signaling pathways involved in FAK signaling include the Jun N-terminal kinases (JNK) survival pathway, and the phosphoinositide 3-kinase (PI3K)/Akt pathway [ 17 ]. PI3K/Akt controls cell proliferation, survival, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ITGB4 has been suggested to be up-regulated in multiple tumors and contribute to tumor progression by promoting proliferation, invasion and EMT process [ 41 , 42 ]. A previous study showed that ITGB4 affected anoikis through interacting with EGFR in hepatocellular carcinoma [ 25 ]. ITGB4 was found to trigger the activation of downstream transmembrane protein kinases, including FAK, to protect against anoikis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITGB4 belongs to the integrin family and has been reported to influence carcinoma progression via modulating anoikis. Focal adhesion kinase (FAK) is a protein tyrosine kinase that mediates cell adhesion, and the activation of FAK can ligate conformation of integrin to promote cell proliferation via downstream phosphatidylinositol 3-kinase (PI3K)/Protein kinase B (AKT) pathway, which finally lead to anoikis resistance [ 25 ]. Growth factor receptor-bound protein 2 (Grb2) is a member of integrin adhesive and critical for the malignant progression of tumors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of the MCF-7 cancer cells with this lectin resulted in the depletion of integrin levels followed by the decrease of active FAK and active Ras. As a consequence, the lack of integrin-mediated cell survival signals sensitized the cell to anoikis (48).…”
Section: Potential Compounds Targeting Integrins For Anti-cancer Apprmentioning
confidence: 99%